2023
DOI: 10.3389/fcvm.2023.1126391
|View full text |Cite
|
Sign up to set email alerts
|

Normothermic ex vivo heart perfusion with NLRP3 inflammasome inhibitor Mcc950 treatment improves cardiac function of circulatory death hearts after transplantation

Abstract: BackgroundThe utilization of donation after circulatory death (DCD) hearts can enlarge the donor pool. However, DCD hearts suffer from serious ischemia/reperfusion injury (IRI). Recent studies found that the activation of NLRP3 inflammasome could play a significant role in organ IRI. Mcc950, which is a novel inhibitor of the NLRP3 inflammasome, can be applied to treat various kinds of cardiovascular diseases. Therefore, we hypothesized that the treatment of mcc950 could protect DCD hearts preserved with normot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Pyroptosis has been shown to play a role in various transplanted organs, including kidneys and the heart [ 193 , 194 ]. In a porcine liver transplantation model, the comparison of cold storage vs. different protocols of machine perfusion strongly suggests a role for NLRP3- and IL-18-related pathways [ 195 , 196 , 197 ].…”
Section: Cell Death In Liver Diseasementioning
confidence: 99%
“…Pyroptosis has been shown to play a role in various transplanted organs, including kidneys and the heart [ 193 , 194 ]. In a porcine liver transplantation model, the comparison of cold storage vs. different protocols of machine perfusion strongly suggests a role for NLRP3- and IL-18-related pathways [ 195 , 196 , 197 ].…”
Section: Cell Death In Liver Diseasementioning
confidence: 99%
“…NLRP3 activation has been shown to significantly contribute to cardiac IRI ( 93 , 94 ). Specifically, in donation after circulatory death (DCD) heart transplantation models, inhibiting the NLRP3-inflammasome has been shown to protect the donor allograft against pyroptosis and apoptosis alike ( 95 ). CD38 inhibition also has the potential to prevent the NLRP3-inflammasome formation and have similar effects on mechanisms of programmed cell-death.…”
Section: Clinical Applications Of Cd38 Mediated Iri and Modulationmentioning
confidence: 99%
“…76 Furthermore, NLRP3 (NOD-, LRR-and pyrin domain-containing 3) inflammasome inhibitors have demonstrated significant therapeutic effects in combating ROS and mitigating oxidative stress in myocardial cells. In a study by Xu et al 77 using donor-heart rats to investigate IR injury in hearts donated after circulatory death (DCD), it was found that intravenous administration of the NLRP3 inhibitor MCC950 in rats could reduce the inflammatory response and oxidative stress levels in DCD hearts preserved with normothermic ex vivo heart perfusion, effectively countering cardiac IR injury. Research by Sun et al 78 revealed that MCC950 treatment markedly reduced the myocardial infarct area, alleviated pathological changes in myocardial tissue, increased left ventricular development pressure, and improved the levels of the maximum rise/decrease rate of left ventricular pressure.…”
Section: Mechanisms Of Macrophage Involvement In Myocardial Ischemia-...mentioning
confidence: 99%